Comparative Comparative Analysis of Islamic Bank Health Levels Using the RBBR and SCnP Methods (2021-2025) - Kurnia Dwi Lestari; Nasrulloh Nasrulloh; Arroyyan Ramly (MASI Mandiri Edukasi, 2026)
This study aims to analyze the financial soundness and Sharia conformity of Islamic commercial banks using the Risk-Based Bank Rating (RBBR) and Sharia Conformity and Profitability (SCnP) approaches. This research employs a quantitative descriptive method using secondary data derived from financial statements of Bank Syariah Indonesia (BSI), Bank Mega Syariah (BMS), and Bank Muamalat Indonesia (BMI) during the 2021–2025 period. The results indicate that BSI demonstrates the most consistent and superior performance, achieving a very strong financial condition under the RBBR method and maintaining a balanced position in the SCnP model. Meanwhile, BMS shows fluctuating performance, and BMI exhibits high Sharia compliance but relatively low profitability. These findings imply that the integration of financial and Sharia-based performance indicators is essential to provide a more comprehensive and accurate evaluation of Islamic banking performance.